Cerebral arterial collateral status, but not venous outflow profiles, modifies the effect of intravenous tissue plasminogen activator in acute ischemic stroke - Elif Sarionder Gencer; Ezgi Yilmaz; Ethem Murat Arsava; Rahsan Gocmen; Mehmet Akif Topcuoglu (Brain Circulation)
BACKGROUND: The role of arterial collateral and venous outflow status on the response to intravenous tissue plasminogen activator (IV-tPA) has not been sufficiently clarified in acute major cerebral occlusions. PATIENTS AND METHODS: A total of 130 patients (mean age: 71 years; 73 females) with acute middle cerebral artery M1/M2 segment or terminal internal carotid artery occlusion treated solely with IV-tPA were analyzed. Regional leptomeningeal score (rLMC) was used for cerebral arterial collateral scoring, and the cortical vein opacification score (COVES) and modified Prognostic Evaluation based on Cortical vein score difference In Stroke (PRECISE) superficial and deep scores were used for venous outflow profile. Exploratory logistic models for response to IV-tPA [positive response: National Institutes of Health Stroke Scale (NIHSS) decrease 4 (or decrease to 0) at 24 h; dramatic response: NIHSS decrease ≥8 (or decrease to 0 or 1)], functional outcome (modified Rankin’s score 0–1 as “excellent” and 0–2 “good”) and tPA-associated hemorrhagic transformation were constructed. RESULTS: IV-tPA efficacy was positive in 47% and dramatic in 32%. Dramatic response was linked to better arterial collateral status (exp[B] =1.115 [95% confidence interval (CI), 1.016–1.223]). Excellent outcome was noted in 26% and good in 45%. One-point increase in rLMC score independently increased good prognosis (exp[B] =1.209 [1.034–1.412]). Patients with good prognosis had higher (by 0.5 points) modified PRECISE deep score (P = 0.047) and less frequent nonsufficient modified PRECISE deep score (0–2) (P = 0.017) in univariate analyses. However, these associations failed to survive in multiple regression. Any type tPA-associated cerebral hemorrhagic transformation was observed in 23% and parenchymal hemorrhage type 2 in 5.4%. While rLMC score showed a borderline strength correlation to hemorrhage (exp[B] =0.899 [95% CI, 0.808–1.001]), outflow scores not. CONCLUSION: While arterial collateral status modifies the effect of tPA in acute anterior circulation major artery occlusions, venous outflow capacity is not so critical.